PENGEMBANGAN DESAIN WEB INTERAKTIF KULINER NUSANTARA BERBASIS KEARIFAN LOKAL KEDAERAHAN (STUDI KASUS KULINER KHAS KABUPATEN KUDUS) - Agus Setiawan; Henry Bastian (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2019)
Development of Interactive Archipelago Culinary Web Design Based on Local Wisdom of Regionalism (Case Study of Typical Culinary of Kudus Regency). This study seeks to inventory, describe and package local cultural values related to the typical Kudus culinary, as an ingredient to be further developed in a learning model and strengthening the creative economy of UMKM in Kudus Regency. How about interactive web media about Kudus special culinary to support the UMKM creative economy in Kudus Regency. So that they know and understand interactive web media about Kudus's unique culinary efforts to support the creative economy of UMKM in Kudus Regency.Contributions to making cultural values the main attraction in the creative culinary economy can be identified local cultural values in the culinary destination. With this study, the packaging of cultural values combined with a creative economy in the culinary field is expected to boost the tourism activities sector which has a positive impact on the social, economic and cultural fields. The research method uses more concrete qualitative methods looking at the aspects studied and expected outcomes. Outputs of the Study are Nusantara Culinary Interactive Web Media Based on Local Wisdom of the Region (Typical Culinary Case Study of Kudus Regency)